La formación investigativa de los maestros en formación a partir de la estrategia de semilleros de investigación (2019)
This article of reflection focuses on the subject of research training through the modality of investigation seedbed, in the program of Bachelor in Basic Education with emphasis in Mathematics, Humanities and Spanish Language, of the Faculty of Distance Studies of the UPTC. A conceptual analysis of the investigation seedbed is made and after the progress of the program in this matter is evidenced. Finally, there are some challenges to be addressed in the immediate future, taking into account the investigative dynamics of higher education and the regional and national educational contexts, in which the teachers in training are part of the groups of seedbed perform.